Meta Analisis Pengaruh Model Pembelajaran Scramble Dalam Meningkatkan Hasil Belajar Peserta Didik Sekolah Dasar - Rustam, Ahmad; Ekadayanti, Waode; Anidi; Ahmad (Arden Jaya Publisher, 2023)
The purpose of this study is to provide an overview of how the scramble learning paradigm is applied in classroom instruction. A learning approach called Scramble gives students the tools to look for, organize, and find learning experiences that are more tangible and applicable to their everyday lives. Thus, the purpose of this research was to offer references on learning models that, when used in the classroom, might enhance student learning results. In this study, effect size estimations are combined with meta-analysis. For this study, information was gathered via reading and perusing a number of scramble-related periodicals. Because it involves numerical computations, the meta-analysis that was employed is quantitative. Students are therefore able to comprehend the connection between ideas and how they apply to real-world situations through scrambling learning. Ten articles with information on scramble learning were the source of this study material. In a descriptive sense, it illustrates how the learning model affected the average from 51.0160 to 85.5000. The statistics from the pretest and posttest show a substantial difference. The scramble learning approach was found to have an impact on the learning outcomes of primary school students.